Factors influencing the time-intensity curve analysis of contrast-enhanced ultrasound in kidney transplanted patients: Toward a standardized contrast-enhanced ultrasound examination - Friedl, Sarah; Jung, Ernst Michael; Bergler, Tobias; Tews, Hauke C.; Banas, Miriam C.; Banas, Bernhard; Putz, Franz Josef (Frontiers in Medicine, 2022)
Background Time-intensity curve analysis (TIC analysis) based on contrast-enhanced ultrasound (CEUS) provides quantifiable information about the microcirculation of different tissues. TIC analysis of kidney transplantations is still a field of research, and standardized study protocols are missing though being mandatory for the interpretation of TIC parameters in the clinical context. The aim of this study was to evaluate the impact of different sizes and forms of regions of interest (ROIs) on the variance of different TIC parameters and the level of interoperator variance between the different ROI methods in kidney transplantations. Methods In 25 renal transplanted patients, 33 CEUS of the transplanted kidney were performed, and TIC analysis with ROIs sized 5 mm2 (ROI5), 10 mm2 (ROI10), and ROIs circumscribing the outlines of anatomical regions (ROIAnat) were analyzed based on CEUS examination. The TIC analysis was repeated by a second independent operator for ROI5 and ROIAnat. Results Statistical analysis revealed significant differences between TIC parameters of different ROI methods, and overall, the interoperator variance was low. But a greater ROI surface (ROI10) led to higher values of the intensity parameters A and AUC compared with ROI5 (p < 0.05). The difference in the ROI form led to high variation of certain TIC parameters between ROI5 and ROIAnat in the myelon [intraclass correlation coefficient (A, ICC = 0.578 (0.139–0.793); TIC parameter (TTP); and ICC = 0.679 (0.344–0.842) (p < 0.05)]. A mean variation of 1 cm of the depth of ROI5 in the cortex did not show significant differences in the TIC parameters, though there was an impact of depth of ROIAnat on the values of TIC parameters. The interoperator variance in the cortex was low and equal for ROI5 and ROIAnat, but increased in the myelon, especially for ROIAnat. Furthermore, the analysis revealed a strong correlation between the parameter AUC and the time interval applied for the TIC analysis in the cortex and myelon (r = 0.710, 0.674, p < 0.000). Conclusion Our findings suggest the application of multiple ROIs of 5 mm2 in the cortex and medulla to perform TIC analysis of kidney transplants. For clinical interpretation of AUC, a standardized time interval for TIC analysis should be developed. After the standardization of the TIC analysis, the clinical predictive value could be investigated in further studies.